The State of Urban Governance and Urban Planning: Bridging the Participation Gap for Marginalised Communities - Durai, Kalpana (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 2 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2024)
Urbanisation in India has been rapid, significantly impacting urban governance and planning, particularly for marginalised communities. Despite contributing substantially to the national GDP, Indian cities face challenges such as inadequate infrastructure, environmental degradation, and housing shortages, which disproportionately affect vulnerable populations. The constitutional mandate for inclusive governance often falls short in practice, leading to gaps in public participation in urban planning. Climate change exacerbates these issues, intensifying the need for robust climate adaptation strategies and inclusive governance. This paper examines the state of urban governance and planning in India, highlighting the participation gaps for marginalised communities and the urgent need for sustainable and inclusive urban development practices. Through an analysis of governance structures, planning mechanisms, and case studies, the paper underscores the importance of climate justice and community engagement in building resilient urban environments. It calls for adopting global best practices tailored to the Indian context to ensure equitable and sustainable urban growth.